Projection-TAGs enable multiplex projection tracing and multi-modal profiling of projection neurons - Lite Yang; Fang Liu; Hannah Hahm; Takao Okuda; Xiaoyue Li; Yufen Zhang; Vani Kalyanaraman; Monique R. Heitmeier; Vijay K. Samineni (Nature Communications)
Abstract Single-cell multiomic techniques have sparked immense interest in developing a comprehensive multi-modal map of diverse neuronal cell types and their brain-wide projections. However, investigating the complex wiring diagram, spatial organization, transcriptional, and epigenetic landscapes of brain-wide projection neurons is hampered by the lack of efficient and easily adoptable tools. Here we introduce Projection-TAGs, a retrograde AAV platform that allows multiplex tagging of projection neurons using RNA barcodes. By using Projection-TAGs, we performed multiplex projection tracing of the cortex and high-throughput single-cell profiling of the transcriptional and epigenetic landscapes of the cortical projection neurons in female mice. Projection-TAGs can be leveraged to obtain a snapshot of activity-dependent recruitment of distinct projection neurons and their molecular features in the context of a specific stimulus. Given its flexibility, usability, and compatibility, we envision that Projection-TAGs can be readily applied to build a comprehensive multi-modal map of brain neuronal cell types and their projections.